2007
DOI: 10.1002/gps.1804
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 6‐week treatment response to escitalopram pharmacotherapy in late‐life major depressive disorder

Abstract: SUMMARYObjective-Approximately half of older patients treated for major depressive disorder (MDD) do not achieve symptomatic remission and functional recovery with first-line pharmacotherapy. This study aims to characterize sociodemographic, clinical, and neuropsychologic correlates of full, partial, and non-response to escitalopram monotherapy of unipolar MDD in later life.Methods-One hundred and seventy-five patients aged 60 and older were assessed at baseline on demographic variables, depression severity, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 41 publications
4
51
4
Order By: Relevance
“…We found no evidence that anxiety affected response to second generation antidepressant treatment in placebo-controlled trials of major depression in older adults. Our findings differ from two prior open-label antidepressant studies in late life depression (Flint and Rifat, 1997;Saghafi et al, 2007), and a randomized trial using a clinical management inter- Figure 1. A meta-analysis of ITT/LOCF response rates to drug and placebo in anxious and non-anxious patients with late life major depression.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…We found no evidence that anxiety affected response to second generation antidepressant treatment in placebo-controlled trials of major depression in older adults. Our findings differ from two prior open-label antidepressant studies in late life depression (Flint and Rifat, 1997;Saghafi et al, 2007), and a randomized trial using a clinical management inter- Figure 1. A meta-analysis of ITT/LOCF response rates to drug and placebo in anxious and non-anxious patients with late life major depression.…”
Section: Resultscontrasting
confidence: 80%
“…Flint and Rifat (1997) in an observational study of 101 older depressed patients, found anxious patients were less responsive to 6 weeks of nortriptyline than their less anxious counterparts. Saghafi et al (2007) examined predictors of response to a 6-week open-label study of escitalopram in 175 patients 60 years and older, and reported higher mean pretreatment anxiety scores in non-responders than in full or partial responders. In a 4-month study of 215 depressed elders in primary care, the PROSPECT study (Alexopoulos et al, 2005) found anxious patients were less responsive to a clinical management intervention than non-anxious patients but level of anxiety did not predict response to usual care.…”
Section: Introductionmentioning
confidence: 97%
“…An initial meta-analysis including trials published up to August 2006 did not find any impact on treatment outcome of increased anxiety symptoms in late-life depression (Nelson et al, 2009). More recent studies, however, all point to negative effects of pre-treatment anxiety levels on treatment outcome in terms of a delayed or reduced response as well as a higher chance of relapse (Dew et al, 1997;Flint and Rifat, 1997;Andreescu et al, 2007;Saghafi et al, 2007;Greenlee et al, 2010). The only two studies examining the impact of comorbid anxiety disorders in late-life depression showed a delayed response (Mulsant et al, 1996;Hegel et al, 2005).…”
Section: Implications/interpretation/conclusionmentioning
confidence: 91%
“…Study participants were drawn from multiple open-label treatment studies of LLD at the University of Pittsburgh's Advanced Center for Interventions and Services Research for the Study of Late Life Mood Disorders. Comprehensive protocols for these studies are detailed elsewhere (Saghafi et al, 2007; University of Pittsburgh, National Institutes of Health, 2008Health, , 2009Health, , 2010. Briefly, patients were ⩾ 60 years old, and identified as suffering from major depression using the Structured Clinical Interview for DSM-IV disorders.…”
Section: Methodsmentioning
confidence: 99%